Late‐onset hemophagocytic lymphohistiocytosis with neurological presentation. Issue 11 (12th September 2017) - Benezech, Sarah; Walzer, Thierry; Charrier, Emily; Heidelberg, Damien; De Saint‐Basile, Geneviève; Bertrand, Yves; Belot, Alexandre
Key Clinical Message: Missense mutations in genes involved in familial hemophagocytic lymphohistiocytosis can delay the onset of this life‐threatening disease. In children and adults, early recognition of aspecific features as neurological symptoms is crucial as urgent treatment is required. Abstract : Missense mutations in genes involved in familial hemophagocytic lymphohistiocytosis can delay the onset of this life‐threatening disease. In children and adults, early recognition of aspecific features as neurological symptoms is crucial as urgent treatment is required.